Highlights of the visit to the King Mongkut’s University of Technology Thonburi (KMUTT), Thailand/ Fathiah Abdullah ... [et al.] - Abdullah, Fathiah; Abdul Rahim, Puteri Rohani Megat; Abdul Rahman, Norhafizah; Ahmad Salleh, Khairulliza; Ahmad Yahya, Naimah; Ramli, Khalijah (2024)
An official visit was made on November 1, 2023 to King Mongkut’s University of Technology Thonburi (KMUTT) by six Heads of Study Centers, UiTM Perak Branch. The main goal of the visit is to be able to have strategic industry-university collaboration between the two universities prior to signing of a memorandum of understanding. Being the host and finding a platform for future collaboration, KMUTT divided the parties from the two universities into three main groups namely built environment, business, language studies and computing, informatics, and mathematics. The participants involved during this session are listed below.